Long term study of the blazar S5 0716+714: investigating a turbulent jet at all wavelengths - Podobnik, F.; Manganaro, M.; Jormanainen, J.; Lindfors, E.; Bonnoli, G.; Paoletti, R.; Jorstad, S.; Kiehlmann, S.; Agudo, I.; Elsasser, D.; Lorey, C.; Raiteri, C.; et al. (Italy, 2025)
The blazar S5 0716+714 is an intermediate BL Lacertae object remarkable for its variability in many energy bands. It was discovered by MAGIC in the very-high-energy (VHE) gamma-ray range in 2008. Later in 2015 an impressive electric vector polarization angle (EVPA) swing was detected in connection with a multiwavelength flaring event including the VHE gamma-ray band. This generated interest in further studies of the jet of this source and its electromagnetic emission at all wavelengths. Since then, MAGIC has monitored the source in coordination with other observatories and here we present the long-term study using data from 2015 to 2022 in a MWL context. The data set also includes the extraordinary flaring activity of 2017, so far the historical maximum detected for this source in the optical and VHE gamma-ray band.